2024
DOI: 10.1590/1807-1929/agriambi.v28n3e272197
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of irrigation in millet crop under salt stress

Francisco H. R. Costa,
Geocleber G. de Sousa,
José M. dos P. Lima
et al.

Abstract: The semi-arid region faces problems related to water deficit and the presence of brackish water that compromise crop performance. Therefore, irrigation frequency can enhance the growth of agricultural crops of interest even under salt stress conditions. In this context, the objective of the present study was to evaluate different irrigation frequencies with water of higher and lower salinity on the agronomic performance of millet. The experiment was conducted from September to November 2020, in the experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…On the other hand, [43] showed a similar trend to that found in the present study, where plants under salt stress showed greater stalk biomass accumulation. For panicle mass, the authors of [44] evaluated the use of high-salinity water associated with 100% of the recommended dose in millet cultivation and found similarity to the results observed in the present study.…”
Section: Eer Reviewsupporting
confidence: 86%
“…On the other hand, [43] showed a similar trend to that found in the present study, where plants under salt stress showed greater stalk biomass accumulation. For panicle mass, the authors of [44] evaluated the use of high-salinity water associated with 100% of the recommended dose in millet cultivation and found similarity to the results observed in the present study.…”
Section: Eer Reviewsupporting
confidence: 86%